Overestimation of Crop Root Biomass in Field Experiments Due to Extraneous Organic Matter - Hirte, Juliane; Leifeld, Jens; Abiven, Samuel; Oberholzer, Hans-Rudolf; Hammelehle, Andreas; Mayer, Jochen (Frontiers in Plant Science, 2017)
Root biomass is one of the most relevant root parameters for studies of plant response to environmental change, soil carbon modelling or estimations of soil carbon sequestration. A major source of error in root biomass quantification of agricultural crops in the field is the presence of extraneous organic matter in soil: dead roots from previous crops, weed roots, incorporated above ground plant residues and organic soil amendments, or remnants of soil fauna. Using the isotopic difference between recent maize root biomass and predominantly C3-derived extraneous organic matter, we determined the proportions of maize root biomass carbon of total carbon in root samples from the Swiss long-term field trial “DOK”. We additionally evaluated the effects of agricultural management (bio-organic and conventional), sampling depth (0 - 0.25, 0.25 - 0.5, 0.5 - 0.75 m) and position (within and between maize rows), and root size class (coarse and fine roots) as defined by sieve mesh size (2 and 0.5 mm) on those proportions, and quantified the success rate of manual exclusion of extraneous organic matter from root samples. Only 60 % of the root mass that we retrieved from field soil cores was actual maize root biomass from the current season. While the proportions of maize root biomass carbon were not affected by agricultural management, they increased consistently with soil depth, were higher within than between maize rows, and were higher in coarse (> 2 mm) than in fine (≤ 2 mm and > 0.5) root samples. The success rate of manual exclusion of extraneous organic matter from root samples was related to agricultural management and, at best, about 60 %. We assume that the composition of extraneous organic matter is strongly influenced by agricultural management and soil depth and governs the effect sizes of the investigated factors. Extraneous organic matter may result in severe overestimation of recovered root biomass and has, therefore, large implications for soil carbon modelling and estimations of the climate change mitigation potential of soils.